2015
DOI: 10.1179/1476830515y.0000000038
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate enhances clearance of phosphorylated tau in primary neurons

Abstract: In this study, we show that EGCG enhances the clearance of AD-relevant phosphorylated tau species in primary neurons. Interestingly, this result appears to be independent of both Nrf2 activation and enhanced autophagy - two previously reported mechanisms of phytochemical-induced tau clearance. EGCG did significantly increase expression of two autophagy adaptor proteins. Taken together, these results demonstrate that EGCG has the ability to increase the clearance of phosphorylated tau species in a highly specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 66 publications
2
34
0
1
Order By: Relevance
“…To confirm that EGCG binds to amyloid fibrils of tau, and that inhibition of tau by EGCG is not the result of indirect effects, [16][17][18] we confirmed binding of EGCG to recombinant fibrils of tau by ITC ( Fig. 1a).…”
Section: Egcg Disaggregates Tau By Stoichiometric Binding To Fibrilsmentioning
confidence: 75%
See 2 more Smart Citations
“…To confirm that EGCG binds to amyloid fibrils of tau, and that inhibition of tau by EGCG is not the result of indirect effects, [16][17][18] we confirmed binding of EGCG to recombinant fibrils of tau by ITC ( Fig. 1a).…”
Section: Egcg Disaggregates Tau By Stoichiometric Binding To Fibrilsmentioning
confidence: 75%
“…Epigallocatechin gallate (EGCG), a small molecule natural product in green tea, inhibits aggregation of numerous amyloid proteins and, despite their tremendous stability, disaggregates fibrils of some amyloids into smaller units. [11][12][13][14][15] Evidence suggesting that EGCG disaggregates fibrils of tau includes studies in primary rat neurons showing that EGCG enhances clearance of phosphorylated tau, 16 although the reported effects of EGCG are somewhat pleiotropic and range from the inhibition aggregation to altered post-translational modification. 17,18 Here, we sought to illuminate the effects direct binding of EGCG to AD-tau by single-particle cryoEM structure determination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catechin and its analogs are flavonoid polyphenols that are abundant in green tea. Among them, epigallocatechin gallate (EGCG) reportedly inhibits Aβ production via α-secretase activation 52) and β-secretase inhibition, 53) inhibits Aβ aggregation, 54) promotes Aβ 55) and phosphorylated tau 56) clearance via autophagy, 55) inhibits tau aggregation, 57) protects neural cells from oxidative stress and Aβ-induced neurotoxicity, 58,59) inhibits AChE activity, 60) and promotes neurogenesis. 61,62) In addition, more than 10 clinical trials have been conducted on EGCG or green tea, 63) and some have shown efficacy in improving cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Bieschke et al showed that EGCG converted the large mature Aβ fibrils into smaller forms with no toxicity for mammalian cell [26]. A recent study conducted by Chesser et al , proved that EGCG in DIV8 primary rat cortical neurons, was able to enhance the clearance of AD-relevant phosphorylated tau species, indicating that EGCG could be used as an adjuvant agent for AD’s treatment [27]. Similar findings were obtained by Chang et al The authors demonstrated that EGCG reduced β-amyloid (Aβ) accumulation in M146 L and CHO cells [28].…”
Section: Introductionmentioning
confidence: 99%